2017
DOI: 10.12659/msm.904549
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Calcitonin Gene-Related Peptide Inhibits Hyperoxia-Induced Alveolar Epithelial Type II Cells Apoptosis, Oxidative Stress, and Reactive Oxygen Species (ROS) Production by Enhancing Notch 1 and Homocysteine-Induced Endoplasmic Reticulum Protein (HERP) Expression

Abstract: BackgroundLung alveolar epithelial type II cells (AEC II) are the most important stem cells in lung tissues, which are critical for wound repair of bronchopulmonary dysplasia (BPD). This study investigated the effects of calcitonin gene-related peptide (CGRP) on AEC II cells exposed to hyperoxia.Material/MethodsNeonatal rat AEC II cells were isolated and identified by detecting surfactant protein C (SP-C). Three small interfering RNAs targeting Notch 1 were synthesized and transfected into AEC II. A hyperoxia-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Some evidence suggests that CGRP release is a response to oxidative stress or cerebral energy disequi librium and might be part of an adaptive response, thereby challenging the perception that CGRP is the patho physiological trigger of migraine. For example, CGRP has antioxidant and anti inflammatory actions [250][251][252][253] , sup porting the hypothesis that its release mediates an adap tive response to oxidative stress and/or energy deficiency. The idea that CGRP increases endogenous energy avail ability for the brain is also supported by rodent studies in which CGRP inhibited insulinstimulated glucose transport 254 , decreased tolerance to glucose in the GTT without altering plasma insulin levels 255 , inhibited muscle glycogen synthesis and caused insulin resistance upon activation of skeletal muscle sensory nerves 256 .…”
Section: Metabolic Functions Of Cgrp and Pacapmentioning
confidence: 95%
“…Some evidence suggests that CGRP release is a response to oxidative stress or cerebral energy disequi librium and might be part of an adaptive response, thereby challenging the perception that CGRP is the patho physiological trigger of migraine. For example, CGRP has antioxidant and anti inflammatory actions [250][251][252][253] , sup porting the hypothesis that its release mediates an adap tive response to oxidative stress and/or energy deficiency. The idea that CGRP increases endogenous energy avail ability for the brain is also supported by rodent studies in which CGRP inhibited insulinstimulated glucose transport 254 , decreased tolerance to glucose in the GTT without altering plasma insulin levels 255 , inhibited muscle glycogen synthesis and caused insulin resistance upon activation of skeletal muscle sensory nerves 256 .…”
Section: Metabolic Functions Of Cgrp and Pacapmentioning
confidence: 95%
“…MDA, as a major product of membrane lipid peroxidation, is also an injury marker that reflects the extent of cell injury. Additionally, MDA content is an important index that reflects membrane lipid peroxidation (45). Thus, the present study detected the change in both SOD activity and MDA content prior to and following LBP treatment in H 2 O 2 -injured cells.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies also revealed that hyperhomocysteinemia causes apoptosis of type II alveolocytes due to the development of oxidative stress in them [1,10]. Hyperhomocysteinemia and folate deficiency are at risk of developing lung cancer due to impaired DNA synthesis and methylation [19].…”
Section: Discussionmentioning
confidence: 99%